Uniform Convergence of Fourier Series on Compact Subsets - Kucukaslan, M.; Abdullayev, F. G. (Sarajevo Journal of Mathematics, 2024)
In this paper, the speed of approximation of ω _n(B;f,z) to zero has been calculated by using analytic and geometric properties of the boundary of the given region, where B is a subset of G (a finite simpy connected domain bounded by a Jordan curve) and ω _n= f(z)-S_n(f,z), zB. 2000 Mathematics Subject Classification. 41A10, 30E10, 42A16